2015
DOI: 10.1038/srep14536
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal domain wall formation in elongated assemblies of ferromagnetic nanoparticles

Abstract: Through evaporation of dense colloids of ferromagnetic ~13 nm ε-Co particles onto carbon substrates, anisotropic magnetic dipolar interactions can support formation of elongated particle structures with aggregate thicknesses of 100–400 nm and lengths of up to some hundred microns. Lorenz microscopy and electron holography reveal collective magnetic ordering in these structures. However, in contrast to continuous ferromagnetic thin films of comparable dimensions, domain walls appear preferentially as longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…We have chosen to perform molecular dynamics at low temperature instead of a simple energy minimization, as it gives a physical meaningful path between the starting configuration and the final configuration, and allow us to later include the motion of the particles. 27 We use values for l and for the moment of inertia I of the nanoparticles corresponding to a type of cobalt nanoparticles (NPs) as used by Var on et al 24 The particles have diameter of r ¼ 15 nm, and magnetic saturation M s ¼ 1:4 Â 10 6 A/m, which leads to a magnetic moment of l ¼ 2:47 Â 10 À18 Am 2 . The density of cobalt is q ¼ 8:9 Â 10 3 kg=m 3 , leading to a moment of inertia of I ¼ 3:54 Â 10 À37 kg m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have chosen to perform molecular dynamics at low temperature instead of a simple energy minimization, as it gives a physical meaningful path between the starting configuration and the final configuration, and allow us to later include the motion of the particles. 27 We use values for l and for the moment of inertia I of the nanoparticles corresponding to a type of cobalt nanoparticles (NPs) as used by Var on et al 24 The particles have diameter of r ¼ 15 nm, and magnetic saturation M s ¼ 1:4 Â 10 6 A/m, which leads to a magnetic moment of l ¼ 2:47 Â 10 À18 Am 2 . The density of cobalt is q ¼ 8:9 Â 10 3 kg=m 3 , leading to a moment of inertia of I ¼ 3:54 Â 10 À37 kg m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Lorentz microscopy and electron holography 24 have previously shown that when a longitudinal wall is present, then a reversed field may move the wall in transversal direction. We were also able to show via simulations that disorder in the particle assembly is important to see this effect.…”
Section: The Role Of Disorder In An External Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In low-dimensional (1-2D) systems, electron holography studies have revealed both nearest neighbor and overall FM-like ordering [33] in long and narrow ensembles in both close-packed as well as more disordered nanoparticle ensembles. In thicker nanoparticle structures, long-range AFM-like interactions become important, as evidenced by super-spin domain formation, with sharp 180 degree walls between nearest neighbor cores [34,35]. Experimental evidence for nearest neighbor moment correlations within ordered 3D arrays of magnetic cores was obtained by Faure et al [36], using dynamic magnetometry in combination with Monte-Carlo simulations.…”
Section: Introductionmentioning
confidence: 98%
“…By varying size, shape, geometric arrangement, and spacing of the individual single-domain nanomagnets the strength and sign of the dipolar interaction, favoring either parallel (ferromagnetic) or antiparallel (antiferromagnetic) orientation of the moments in adjacent magnets, can be tuned and lead to new magnetic phenomena. 8,9 Thus, supermagnetism offer a new avenue for design and control in nanoscale magnetic materials and devices, provided the collective magnetic properties can be controlled at the nanoparticle level.…”
mentioning
confidence: 99%